Factors related to voluntary external turnover of nursing professionals - Yvete Carvalho Chaves Balabanian; Maria Inês Monteiro (SciELO, 2019)
ABSTRACT Objective: To analyze the factors related to the turnover of nursing professionals of a public teaching hospital. Method: Descriptive, exploratory, retrospective study with quantitative analysis conducted with workers from a public teaching hospital. The analysis used a data collection instrument from the service, applied at the time of the voluntary resignation of the professional. Results: 223 nursing professionals participated in the study. The factors that led to voluntary turnover were the employment bond, age and the association of both. The majority of professionals were young adults, in a high productivity phase, which increases willingness to seek challenges in the labor market and professional improvements. Conclusion: Turnover is multifactorial and influenced by economic, social and political aspects. Reducing inequalities in working conditions, which generate dissatisfaction, such as different employment bonds for professionals who have the same function and perform the same activities, is fundamental to reduce turnover.